Dielectric characterization of pineapple leaf fibre (PALF) reinforced polydimethylsiloxane (PDMS) composites with varying fibre loading - Abu Bakar, Nur Hidayah; Abu Bakar, Aslina; Ibrahim, Amirudin; Mozi, Aiza Mahyuni; Radzali, Rosfariza; Abd Rahim, Alhan Farhanah; Mohd Faudzi, Najwa; Idris, Azlina (UiTM Press, 2025)
This study investigates the dielectric properties of biofibre-reinforced polymer composites composed of Pineapple Leaf Fibre (PALF) and Polydimethylsiloxane (PDMS), with a focus on varying fibre loadings and the effects of alkaline treatment. Conventional dielectric substrates such as FR4 suffer from rigidity, environmental concerns, and limited tunability. In contrast, PALF-PDMS composites offer a sustainable alternative with adjustable dielectric characteristics. Composites were fabricated via manual mixing, incorporating PALF loadings from 10 wt% to 90 wt%. Alkaline treatment using NaOH enhanced fibre-matrix compatibility by reducing moisture absorption and increasing interfacial polarisation. Results show that treated composites exhibit lower dielectric constants at low fibre loadings but outperform untreated variants at higher loadings. These findings highlight the potential of PALF-PDMS composites as ecofriendly, tunable substrates for flexible electronics and antenna applications.